Arquitectura moderna en Bogotá - Piñón, Helio, 1942-; Hernández Rodríguez, Carlos Eduardo; Fontana, María Pía; Salamanca Ramírez, Óscar Alonso; Bright Samper, Pedro Juan; Mayorga Cárdenas, Miguel Y.; Rojas Farias, Ricardo (Bogotá : UTADEO, Universidad de Bogotá Jorge Tadeo Lozano, Facultad de Artes y Diseño, Programa de Arquitectura, 2016)
A set of essays on the modern architecture in the city of Bogota. The articles are the result of the concerns of the authors around the utility of the buildings that make up the history of modern architecture in the country for the understanding of the problems of the contemporary city. The raised arguments include project dimensions, which includes urban, landscape, building and technique.ʺ--Back cover (translated by Karno Books).
Prólogo / Helio Piñón -- Introducción / Carlos Eduardo Hernández Rodriguez -- La arquitectura y la naturaleza : reflexiones sobre la casa moderna en Bogotá / Óscar Alonso Salamanca Ramírez -- Bogotá : edificios en altura y espacio urbano moderno / Maria Pía Fontana -- Uso y tipo en la arquitectura moderna en Bogotá : el Centro Internacional como proyecto unitario / Pedro Juan Bright Samper -- Hacer centro : habitabilidad, modernidad y centralidad en el centro de Bogotá / Miguel Y. Mayorga Cárdenas -- Fabricar la torre : la evolución tecnica al servicio de la maquina arquitectónica moderna en Bogotá / Ricardo Rojas Fríass.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed April 11, 2018).
JSTOR
Keywords: Architecture -- Colombia -- Bogotá -- History; Modern movement (Architecture) -- Colombia -- Bogotá.; Bogotá (Colombia) -- Buildings, structures, etc; Architecture -- Colombie -- Bogotá -- Histoire; Mouvement moderne (Architecture) -- Colombie -- Bogotá.; Reference; Architecture; Buildings; Modern movement (Architecture); Colombia -- Bogotá; Electronic books; History